Формування стратегії розвитку зовнішньоекономічної діяльності на підприємстві - Пічугіна, Тетяна Сергіївна; Бутенко, Герман Валерійович (НТУ "ХПІ", 2018)
У статті запропоноване авторське бачення на визначення суті розвитку підприємства. Запропоновано класифікацію підходів до стратегічного розвитку зовнішньоекономічної діяльності за такими критеріями: фактор часу; спрямування; зміст, загальна спрямованість на певний сегмент ринку. Розглянуто послідовність формування стратегії розвитку зовнішньоекономічної діяльності підприємства, у результаті чого виокремлено мотиви (формування місії, цілей, завдань підприємства), аналітику (діагностика зовнішніх і внутрі шніх чинників) результати (розробка стратегічних альтернатив) цього процесу, що стало підґрунтям визначення його етапів.

The article proposes an author's vision for determining the essence of enterprise development. The classification of approach es to the strategic development of foreign economic activity according to the following criteria is proposed: time factor; direction; content, general orientation on a certain segment of the market. The sequence of forming the strategy of development of foreign economic activity of the enterprise is considered, as a result of which the motives (formation of the mission, goals, tasks of the enterprise), analytics (diagnostics of external and internal factors), the results (development of strategic alternatives) of this process, which became the basis for determining its stages (first stage – analysis of the external environment, forecasting the future development of the foreign economic activity of the enterprise, the second – the definition of the mission, goals and objectives of the foreign business enterprise, the third – strategic analysis; erytty – modeling of variational scenarios for the development of events and studying the impact of each on the formulated alternative strategies of foreigne conomic activity, the fifth – the choice of the most acceptable strategy of foreign economic activity from the alternative, the sixth – the preparation of the final version of the strategic plan for the development of foreign economic activity, the seventh – on the basis of the strategic plan are developed tactical medium-term plans of foreign economic activity; eighth – operational plans and projects are being developed.
Keywords: стратегічні рішення; ЗЕД; конкурентоспроможність; цінова політика; експорт; імпорт; менеджмент; development; strategy; development strategy; strategic management; foreign economic activity; enterprise